Analisis kelayakan rencana bisnis “Kopi Kayu Manis Ayya” tinjauan aspek rencana keuangan periode 2021 -2025 - Brastoro; Bernadine (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the feasibility of financial plan of Kopi Kayu manis Ayyafor 5 years for the period 2021-2025. The sample of this study is determined based on dataand information from the company's financial statements, in the form of a Balance Sheet,Cash Flow Statement, and Profit and Loss Statements for the 2021 -2025 period. The dataanalysis technique uses investment feasibility methods, namely Payback Period (PP), NetPresent Value (NPV), Internal Rate of Return (IRR) and Profitability Index (PI). Theresults showed that the investment of Kopi Kayu manis Ayya is feasible because based onthe Income Statement Performance for the next 5 years is that generates an increasingprofit every year. Moreover, based on Cash Flow Performance for the next 5 years, thefinal cash flow is always positive and increases every year. While the results of thecalculation using the investment feasibility assessment resulted in an NPV of Rp.281,253,754, Internal Rate of Return (IRR) of 27.22% where this value is greater than theexpected rate of return of 13.47%, Profitability Index (PI) of 1.479004885 with a totalpayback period of 3 years 3 months 10 days, so it can be concluded that the investment isa feasible.